Joel Bakan: Childhood Under Siege. How Big Business Callously Targets Children - Young-Bruehl, Elisabeth (HannahArendt.net, 2012)
Joel Bakan: Childhood Under Siege. How Big Business Callously Targets Children, Free Press, US: Simon and Schuster; UK: The Bodley Head, Random House, 2011